Step-by-step explanation:
5x+7+2x=7(2x+3)-63
We move all terms to the left:
5x+7+2x-(7(2x+3)-63)=0
We add all the numbers together, and all the variables
7x-(7(2x+3)-63)+7=0
We calculate terms in parentheses: -(7(2x+3)-63), so:
7(2x+3)-63
We multiply parentheses
14x+21-63
We add all the numbers together, and all the variables
14x-42
Back to the equation:
-(14x-42)
We get rid of parentheses
7x-14x+42+7=0
We add all the numbers together, and all the variables
-7x+49=0
We move all terms containing x to the left, all other terms to the right
-7x=-49
x=-49/-7
x=+7 - Answer